A leitura musical no processo de formação do violonista: perspectivas a partir dos materiais didáticos utilizados no ensino superior - Costa, Bruno Xavier Marinheiro de Oliveira (2014)
This work presents the results of a survey about the practices, conceptions, beliefs and didactic materials employed by guitar professors through graduation courses of music performance at guitar in Brazilian universities, specially the materials and practices about sight-reading, and aims to contribute to research about teaching of musical instruments, both at Music Education and at Performing Practices. This survey revealed the most used guitar teaching methods at Brazilian universities and the literature search undertaken about the sightreading subject made it possible to draw a state of the art that guided the analysis of those didactic materials, identifying and relating its features with the knowledge base about expertise in problem solving, flow and deliberate practice. Presenting and analyzing the instrument teaching methods used by the aforementioned guitar teachers, their practices and beliefs about the teaching of guitar playing and sight-reading, made it possible to relate literature s knowledge of the subject with teaching approaches, and to state well informed hypothesis about sight-reading relevance to Brazilian guitar playing and teaching. It was made clear that sight-reading valuing manifested itself more in speech than in practice, and issues concerning guitar students suggests that, among many other factors, deficiencies in elementary music education makes that guitar teaching excessively focuses on memorized repertoire teaching and sacrifices more integrative practices like chamber music and sightreading. Seeking to improve the comprehension of this scenario, possibilities of didactic and pedagogical acting and researching are discussed.